(untitled) (Praxis Educativa, 2012)
Argentinian academic literature has naturalized the relationship between the symbol “nation” and the political actors of the ideological authoritarian formation. Starting from the authors that proclaimed the country defense against the ideological threats (communism and anarchism) and the huge immigration at the beginning of 20th century, that literature considers the national request as an easy resource to manipulate the popular will in authoritarian systems. This article examines this supposition critically, analyzing the Malvinas/Falkland cause historically and its emergence in 1982 when the argentinian recovery of the south atlantic islands, and demonstrates that the national request was the legitimate channel of political struggle during the tumultuous Argentinian 20th century.